EFFECT OF THERMOSONICATION ON FERRIC REDUCING ANTIOXIDANT POWER AND THE COLOR OF BERAS KENCUR DRINK - Serly Safitri; Sri Winarti; Luqman Agung Wicaksono; Anugerah Dany Priyanto; Wildan Naufal Esfandiar; Almira Dinar Dhiny (Jurnal Pangan dan Agroindustri, 2022)
ABSTRACT